0022 Understanding the role that state public health agencies can and do play in bullying prevention. (26th April 2015) - Hunt, Rebekah; Schmidt, Ellen; Reiney, Erin
Abstract : Statement of purpose: Bullying is a significant public health problem, and state public health agencies have an important role to play in its prevention. In the 2013 Youth Risk Behaviour Survey (YRBS), 20% of students reported being bullied on school property and 15% reported being electronically bullied in the 12 months preceding the survey. Victimised youth are at increased risk for depression, anxiety, sleep difficulties, and poor school adjustment. Youth who bully others are at increased risk for substance use, academic problems, and violence later in adolescence and adulthood. Methods/Approach: In December 2014, the Children's Safety Network (CSN) developed and administered a bullying prevention environmental scan to state Injury and Violence Prevention and Maternal and Child Health (MCH) directors. The purpose was to determine the extent and nature of state public health agency involvement in bullying prevention to inform the creation of new technical assistance resources. The scan examined state infrastructure and leadership, strengths and challenges of current efforts, knowledge of existing resources, and specific needs for new resources. CSN received scan responses from 41 states. Results: Fifty-five percent of the states that responded to the scan reported that their state public health agency is involved in bullying prevention, although 68% of the states said that their Department of Education leads bullying prevention efforts. Among the strengths noted by states were local work on school policies and coalitions and the availability of data, while challenges included funding, coordination, and getting information on evidence-based practices. Conclusions: The presentation will explain the scan results and describe strategies that state public health agencies can utilise to expand their role in bullying prevention, including strategic plans, policies, coalitions, and task forces. It will also describe evidence-based practices and the important new opportunity for bullying prevention provided by the proposed new Title V MCH National Performance Measure on the reduction of bullying in adolescents ages 12 through 17. Significance and contribution to the field: By preventing bullying, public health professionals can reduce adverse health outcomes and other types of violence and aggression. This presentation supplies participants with the knowledge and tools to increase the effectiveness of state bullying prevention efforts.